Synthesis of reduced graphene Oxide (rgo) for the removal of Tetracycline from aqueous Solutions - Ha, Thi My Trinh (2020)
Chapter 1: Literature review: Overviews on antibiotics in the aspects of classification, current applications in human and veterinary, pollution situation, ecological and environmental impacts, treatment technologies, along with the synthesis and application of rGO in antibiotic adsorption. Chapter 2: Materials and methods: Describes materials, chemicals and methods utilized for the synthesis, characterization and application of rGO in the adsorption tests. Chapter 3: Results and discussion: Refers the main research results, including characterization of rGO, factors influencing the adsorption of TC, adsorption isotherms, and adsorption kinetics. Chapter 4: Conclusions and recommendations: Summarizes the main findings of the present study and suggests future perspectives.